Gamma radiation modified the optical, electrical, and antibacterial characterization of CuONPs doped in polyethylene oxide/polyvinyl alcohol - M.F.H. Abd El-Kader; M.T. Elabbasy (Journal of Materials Research and Technology, 2020)
Various doses of gamma radiation affecting on enhancing the electrical and antibacterial characterization of Polyethylene Oxide/Polyvinyl Alcohol embedded by copper oxide nanoparticles. PEO/PVA/CuONPs nanocomposites films have been exposed to various doses using Indian 60Co gamma cell (2000 Ci). The physical properties of PEO/PVA/CuONPs nanocomposites were investigated via various routes. The electrical properties and antibacterial activity of PEO/PVA/CuONPs after irradiated with gamma were studied. FT-IR results showed rearrangements in the system due to the obvious influence of gamma doses. UV/vis. spectra showed a SPR peak of CuONPs at 281 nm, which is mainly impacted by the dose of irradiation. Dielectric constant and dielectric loss behavior of PEO/PVA/CuONPs nanocomposite has been decreased by increasing frequencies via rising the doses. PEO/PVA/CuONPs nanocomposite exposed to gamma induced an improvement in the antibacterial efficacy. PEO/PVA/CuONPs nanocomposite exposed to gamma make a huge improvement in the both electrical conductivity and antibacterial efficiency and could recommend these compositions for further study in electrical and biomedical applications such as wound dressing and infection control.